POLA KOMUNIKASI RITUAL ORANG TUA-ANAK DALAM PEWARISAN PENGETAHUAN DAN AFEKSI TERKAIT PEKERJAAN DI SEKTOR PERTANIAN PADI - Yogaprasta Adi Nugraha (Prodi Ilmu Komunikasi Universitas Putera Batam, 2020)
Agriculture is one of potential sector that contribute positevely to national income. But Paradoxicaly, the importance of agricutural sector is not followed by their workers regeneration. Rural youth is prefer to go from agricultural work due to several justification such as land conversion, less-benefit, unprestige work, and negative construction by the social system. The objectives of this research are: (1) Identifying the ritual practice in agriculture sector, (2) Identifying the rural-youth involvement in helping their parents in agricultural work, (3) Analyzing corelation between rural youth involvement and rural youth cognitive and affective towards agriculture work. Mixed Method Concurrent was used as research method, taken place in Ciasmara Village from March 2019 to August 2019, 129 youth were taken as research sample. This research found that ritual of Sedekah Bumi still exist in Ciasmara Village, rural – youth still involve in helping their parents in agriculture sector, mostly in harvesting period. Rural youth involvement in agriculture sector correlated to rural – youth cognitive and affentive.